Renewable energy from thermophilic anaerobic digestion of winery residue: Preliminary evidence from batch and continuous lab-scale trials. (August 2016) - Da Ros, C.; Cavinato, C.; Bolzonella, D.; Pavan, P.
Abstract: The winemaking process generates many by-products besides wastewater, mainly grape marcs, grape stalks, and wine lees. Anaerobic digestion is particularly suitable to treat winery waste because of its high content of nutrient-rich organic matter and for its noticeable energetic potential. To date, only results from mesophilic tests have been extensively reported. In this study, potential methane production and kinetic constants were determined by batch trials under thermophilic conditions and compared with mesophilic values already reported in literature. Grape marcs and wine lees appeared to be the most promising substrates with an estimated potential of 0.34 and 0.37 Nm 3 CH4 /kgVSfed, respectively, while grape stalks generated only 0.13 Nm 3 CH4 /kgVSfed . In order to assess the feasibility of a continuous anaerobic digestion process, a lab-scale semi-continuous reactor was constructed. Because of the consumption of buffer capacity, the biological process was difficult to control. On the other hand, biogas was produced when working with a hydraulic retention time of 40 d and with previously fermented grape marcs; a specific biogas production of 0.29 Nm 3 /kgVSfed was observed. The results of the continuous tests were used to calculate the potential energy recovery from grape marcs produced in Italy (808 thousands of tons per year) in terms of heat and electricity; about 245 GWh of heat and 201 GWh of electricity per annum could be generated in Italian scenario. Highlights: Complete study on thermophilic digestion of winery waste by batch and continuous reactors. Potential methane production at 55 °C reached 0.360 Nm 3 /kgVS. Addiction of a co-substrate improved process stability. Application of long HRT and previous fermentation double SGP of marcs.